Sexualidad y minorías sexuales en la provincia de Trujillo en los años de 1980 a 1990. - Alvarado Honorio, Sofia Cosett (2019)
The purpose of this paper was to show the development of sexuality and sexual minorities in the province of Trujillo during the 1980s through newspapers and judicial sentences on seduction, the general objective of this was to explain the development of sexuality and sexual minorities in the province of Trujillo from 1980 to 1990 and had as specific objectives: to analyse the political, economic and social context of Peru and the province of Trujillo in the years from 1980 to 1990, to explain the development of sexuality in the province of Trujillo in the years from 1980 to 1990, and determine the development of sexual minorities in the province of Trujillo in the years from 1980 to 1990. _x000D_ This work developed the population policies that the Peruvian state applied in the province of Trujillo, in addition to how this city strongly opposed pornography, but another sector continued to consume it, the little tolerance that was had for sexual minorities in that decade , which impacted even more with the AIDS epidemic, in addition to the dictum for seduction, it was possible to make visible the long historical time thinking about women who denounced this fact since it did not change since colonial times, this was proven because In the 1980s, whether or not a sentence was favourable continued to depend on the chastity and good moral conduct of the victim. _x000D_ This thesis was based on the historiography of the genre, that of mentalities, and the inductive method, with Trujillanos newspapers as primary sources, such as El Satélite and La Industria and sentences for seduction made in the 1980s. _x000D_ After the work carried out, it is concluded that in the years from 1980 to 1990 the Trujillo population was conservative and that the Catholic church had a great influence on their thinking and behavior, thereby generating the rejection of sexual minorities, but at the same time it was found that this, went to nightclubs, consumed pornography, although the municipality implemented regulations to try to prevent its proliferation, generating a double standard moral.